Adsorption of a silicone‐based surfactant on polyethylene and polypropylene surfaces and its tribologic performance. Issue 19 (8th May 2014) - Song, Junlong; Li, Yan; Cheng, Qiang
ABSTRACT Aqueous silicone‐based surfactants are widely used in the processing of synthetic fibers in textile industries since they enhance a number of functional and processing properties. In this paper the interactions between silicone‐based surfactants and textile‐relevant surfaces (polyethylene and polypropylene) were investigated by quartz crystal microbalance with dissipation and the tribologic performance was evaluated by lateral force microscopy. Our results showed that the more hydrophobic polypropylene surface had higher affinity with silicone‐based lubricants than polyethylene surface. These adsorbed layers provided lubricity in textile materials when subject to shear forces and offered protection to wear and abrasion. This is explained by the fact that the hydrophobic groups in the surfactant molecules interact more effectively with the polypropylene surface via hydrophobic forces. This information will ultimately help to further our understanding on lubrication phenomena in fiber processing. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40838.